Mathematical physical diagnosis of neonatal cardiac dynamics based on dynamic systems and fractal geometry: Clinical validation study (2023)
A mathematical evaluation of neonatal cardiac dynamics was developed. The purpose of this study is to confirm the diagnostic capacity of this methodology to differentiate normal neonatal cardiac and cardiac pathologies through a blind study. For this, 80 Holter records were taken, 10 with evaluation within the limits of normality and 70 with different cardiac pathologies. The conventional evaluations were masked, and the maximum and minimum heart rates were taken every hour and the number of beats/hours, during 21 hours. These values were used to generate the neonatal cardiac attractor, then their fractal dimension was calculated, their occupation spaces were quantified in the fractal space of Box-Counting, determining their physic mathematical diagnosis. The spaces of occupation of neonatal chaotic cardiac attractors measured according to the number of frames occupied by the Box Counting method, differentiate states of normality from acute pathologies, achieving a sensitivity and specificity of 100%, as well as a kappa coefficient of 1. The This study confirms the diagnostic capacity of the methodology developed, from which it is possible to establish geometric differences between the chaotic attractors of normal neonatal cardiac dynamics and with disease. © 2019 Published under licence by IOP Publishing Ltd.